Study on the Coral Reefs of Pulau Pinang, Terengganu and Pulau Satang, Sarawak - Govind Raj, A/L S Ganeson (Universiti Malaysia Sarawak (UNIMAS), 2010)
Assessments of the percentage coral cover caried out at Pulau Pinang and Pulau Satang using the line transect technique showed the reefs status are generally mediocre. A total of 5 stations were surveyed on both islands and 3 stations in Pulau Pinang are mediocre (41 - 45% cover) while one is in good condition (68%). Pulau Satang recorded a percentage coral cover of 41% which is also mediocre. Two main factors contributing to the deterioration of reefs in Pulau Pinang are Acanthaster plancii predation and uncontrolled diving and snorkeling activities. Sedimentation, temperature and salinity are factors contributing to the deterioration of ree£ in Pulau Satang. Eighteen species of corals were identified at both locales; the most dominant species for Pulau Pinang are Acropora halmahelO , A. nobilis and Montipora sp. while Astreopora sp., Favtafavus and Acropora palifera were dominant at Pulau Satang. There is a significant difference of percentage cover between Pulau Pinang and Pulau Satang. In Pulau Satang, TSS ranges from 0.01-0.05 g/L, nitrate ranges from 0-0.02 mg/L, nitrite ranges from 0.02-0 .04 mglL, phosphate ranges from 0.33-1.13 mg/L, pH ranges from 8.0- 10.3 and temperature ranges from 30.0-30.8°C.